What Drives Intention to Use Facebook: An Empirical Study of Vietnamese Users - Thuy, Hoang Dam Luong; Ha, Nguyen Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 36 No 5E, 2020)
This study aims to investigate users’ attitude and intention to use of a social media site in the context of the Facebook platform. A questionnaire survey was conducted to collect data from 134 users of Facebook in Vietnam. Collected data were analyzed by using hierarchical regression analysis. This study points out that trustworthiness and perceived usefulness are the direct predictors of intention to use social media sites such as Facebook. Specifically, trustworthiness is found to have the greatest impact on intention to use Facebook, which is followed by perceived usefulness among Vietnamese users. These findings provide evidence about the value of trust and perceived usefulness that can be considered as direct predictors of behavioural intention to use a product or technology. Moreover, remarkable points are recommended for Facebook developers, business managers and the Vietnamese Government in integrating Facebook as well as other online social media platforms and business strategies. As a result, the study can be helpful for future researchers, managers, practitioners and educators in the area of the Vietnamese social media community.